AN ANALYSIS COMMUNICATIVE LANGUAGE TEACHING - Sri Hardini, Zaini Munawir, Waridah (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2021)
The title of this Independent Research is An analysis of communicative language teaching .The analysis that is carried out is focused only on the communication approach to students or pupils with various methods that will be given. The goal of Communicative Language Teaching is to have one’s students become communicatively competent. While this has been the stated goal of many of the other methods in the communicative approach the notion of what it takes to be communicatively competent is much expanded. Adherents of the communicative approach, which we will consider in this Analysis acknowledge that structures and vocabulary are important. However they feel that preparation for communication will be inadequate if only these are taught. Students may know the rules of language usage, but will be unable to use the language. When we communicate, we use the language to accomplish some function, such arguing, persuading, or promising. More over, we carry out these functions within a social context. A speaker will choose a particular way to express his argument not only based upon his intent and his level of emotion, but also on whom he is addressing and what his relationship with that person is. Furthermore, since communication is a process, it is sufficient for students to simply have knowledge of target language forms, meanings and functions. Students must be able to apply this knowledge in negotiating meaning. It is through the interaction between speaker and listener (or reader and writer) that meaning becomes clear. The listener gives the speaker feedbacks as to whether or not he understands what the speaker has said. In this way, the speaker can revise what he said and try to communicate his intend meaning again, if necessary.